EXPLORATION THE EFFECT OF HIGHER DOSE OF AQUEOUS AND ALCOHOLIC EXTRACTS OF BAMBER FRUIT (CORDIA MYXA ) OF SOME HISTOLOGICAL PARAMETER AND SYMPTOM IN MICE - & et al., Al-Hamdani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimed to explore the safe levels of the aqueous and alcoholic extract of the pamper (Cordia myxa) fruit in used mice, and its effect on vital organs.Various doses of 1000, 2000, 3000, 4000 and 5000 mg/kg  body weight were used in this study for both aqueous and alcoholic extracts for the entire week. The safe doses of aqueous and alcoholic extracts were then used with 1000, 2000 and 3000 mg / kg body weight and continued observation for two weeks. At the end of the experiment, animal weights were taken, mice were then executed and weights of some of important biological organs such as kidney and liver were weighed and examined for histopathological segments. The results of the study did not show any lethal effects due to the use of aqueous and alcohol extracts with low doses concentrations 1000, 2000 and 3000 mg / kg body weight of the animal of the pamber fruit, but some minor side behavior, as well as there is no significant change in the weights of the body of mice. While the histological test of the liver and kidney showed slight discomfort with minor degenerative changes with the depletion of the diabetic protein pellets at the tissue site. After the end of the experiment, animals weights were taken, and mice were then executed and their weights taken from animals and some of its organs were studied with histological changes of important biological organs such as liver and kidneys.